Pemanfaatan Pohon Perekat sebagai Perangkap Lalat Musca domestica - Vika Dwi Febriana; Sarjito Eko Windarso; Haryono Haryono (Poltekkes Kemenkes Yogyakarta, 2020)
Diarrhea is still a public health problem in Indonesia with relatively high morbidity and mortalityrate and potential to cause outbreak. One of the causes of diarrhea is contamination of Muscadomestica flies. Various types of fly control can be implemented. This study proposed an innovationdevice on fly control, called “adhesive tree”, which is categorized to physical mechanicalcontrol. The purpose of this study was to reveal the capability of this device at chicken farm inPlalangan Village of Pendowoharjo, Sleman. The study was quasi experiment with post testonly control group design. The data were analysed by using independent sample t-test. Theresults showed that adhesive tree, in average, were able to trap more flies than conventionaladhesive paper did. i.e. 24 flies compared to 4 flies. The p-value obtained from statistical analysiswas 0,001 which confirms that the difference is significant. Therefore, adhesive tree hasbetter ability than conventional adhesive paper in trapping Musca domestica flies.